The Growth of Entire Functions Defined by Laplace–Stieltjes Transforms Related to Proximate Order and Approximation. (9th April 2020) - Tang, Wen Ju; Chen, Jian; Xu, Hong Yan
Abstract : In this article, we discuss the growth of entire functions represented by Laplace–Stieltjes transform converges on the whole complex plane and obtain some equivalence conditions about proximate growth of Laplace–Stieltjes transforms with finite order and infinite order. In addition, we also investigate the approximation of Laplace–Stieltjes transform with the proximate order and obtain some results containing the proximate growth order, the error, A n ∗, and λ n, which are the extension and improvement of the previous theorems given by Luo and Kong and Singhal and Srivastava.